Variabel makroekonomi dan indeks harga saham gabungan: Studi pada sektor pertambangan yang terdaftar di Bursa Efek Indonesia - Putri, Intan Yunita Aldayanti; Nugroho, Hendrato Setiabudi (Journal of Economics Research and Policy Studies, 2024)
Investing in the capital market is one of the popular choices among investors, both for beginners and experienced ones, to get capital gains. The downstream program that increases economic added value makes the mining sector, metal, mineral, and other sub-sectors, listed on the Indonesian Stock Exchange as an alternative investment that can provide attractive profits. This study aims to test the effect of macroeconomics, including inflation, the Rupiah exchange rate, interest rates, and the significant amount of money supply on the movement of the stock price index. The study was quantitative research with historical data collection techniques through the official websites of the Indonesian Stock Exchange, Bank Indonesia, and Badan Pusat Statistik for 2021-2023. The study sample consisted of 27 issuers that met certain criteria according to the purposive sampling technique. The results of the data analysis showed that simultaneously, the four independent variables had a positive and significant effect on the 2021-2023 Composite Stock Price Index.